2016
DOI: 10.18632/oncotarget.10159
|View full text |Cite
|
Sign up to set email alerts
|

Gypenoside L inhibits autophagic flux and induces cell death in human esophageal cancer cells through endoplasm reticulum stress-mediated Ca2+ release

Abstract: Esophageal cancer is one of the leading cause of cancer mortality in the world. Due to the increased drug and radiation tolerance, it is urgent to develop novel anticancer agent that triggers nonapoptotic cell death to compensate for apoptosis resistance. In this study, we show that treatment with gypenoside L (Gyp-L), a saponin isolated from Gynostemma pentaphyllum, induced nonapoptotic, lysosome-associated cell death in human esophageal cancer cells. Gyp-L-induced cell death was associated with lysosomal swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…Endoplasmic reticulum and mitochondrial are important organelles to maintain normal cell function (Nami et al, ; Liao et al, ). The unfolded protein response (UPR) is a cellular signaling pathway in the ER that is activated in response to overloading of unfolded or misfolded peptide chains.…”
Section: Introductionmentioning
confidence: 99%
“…Endoplasmic reticulum and mitochondrial are important organelles to maintain normal cell function (Nami et al, ; Liao et al, ). The unfolded protein response (UPR) is a cellular signaling pathway in the ER that is activated in response to overloading of unfolded or misfolded peptide chains.…”
Section: Introductionmentioning
confidence: 99%
“…During the course of tumor development, the metabolic pathway of protein metabolism is often disordered, and intracellular homeostasis is disrupted. 31 It has been reported that PSMD4 plays an important role in ubiquitination-related protein metabolism. 21 Studies of patients with multiple myeloma have found that PSMD4 may be associated with adverse outcomes and resistance to bortezomib.…”
Section: Discussionmentioning
confidence: 99%
“…The level of Ca 2+ in cytoplasm was elevated which showed that intrinsic apoptosis was induced. Release of Ca 2+ from endoplasmic reticulum revealed that ER stress may be involved in apoptosis, while further study was still needed to confirm this hypothesis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%